CEL I nuclease digestion for SNP discovery and marker development in common bean (Phaseolus vulgaris L.) - Galeano Mendoza, CH; Gómez, M.; Rodríguez, L.M.; Blair, Matthew W. (Wiley, 2009)
Single nucleotide polymorphisms (SNPs) are the most common sequence difference found in plant genomes, yet they have not been widely exploited for producing molecular markers in common bean (Phaseolus vulgaris L.). The objective of this study was to develop a SNP assay based on a type of heteroduplex mismatch cleavage called EcoTILLING for molecular marker development in this important legume, and apply the assay (i) to the conversion of a sequence-characterized amplified region (SCAR) marker useful for selecting virus resistance (SR2) and (ii) to the screening of SNP polymorphisms in newly developed expressed sequence tag (EST)–based markers. The SNP assay involved heteroduplex mismatch cleavage by a single-strand specific nuclease ‘CEL I’ which was used to uncover two SNPs in the SR2 fragment and 22 SNPs in 37 candidate ESTs, some of which were used in segregation analysis. While developing the SNP techniques we tested several platforms, including LI-COR, nondenaturing polyacrylamide, and agarose gel detection. The agarose gel system was used for SNP genetic mapping in two common bean mapping populations, showing that heteroduplex cleavage is a useful technique for increasing molecular marker number for the crop. Examples are given of mapped SNP markers for the phytic acid pathway gene for myo-inositol-1-phosphate synthase and a drought tolerance–related gene, S-adenosylmethionine decarboxylase.